PENGARUH DIAMETER DAN JUMLAH PAKU TERHADAP KEKUATAN SAMBUNGAN GESER GANDA BALOK KAYU NANGKA (Artocarpus heterophyllus) dan RASAMALA (Altingia excelsa Noronha) DENGAN PELAT BAJA - Sucahyo Sadiyo; Emma Yusrina Wulandari (PERENNIAL, 2012)
The application of nail connection for part of the structural construction in Indonesia is still become the main choice. Connection type that must be counted on seriously for structural construction, are tension, shear and momen connection. Nangka wood is a type of woods that available in sawing or community woods work around Bogor. Rasamala is endemic and unique woods from West Java. Nails as connection are cheap, available and workable. This research objective is to investigate the effect of diameter and amount of nails to double shear connection strength on two type of woods. The results showed that the increase of diameter and amount of nail will rise the capacity of total allowable load per shear plane (RT) or double shear connection strength of nangka woods and rasamala-steel plate, but this phenomena is different for allowable load capacity per nail per shear plane (R) for both of that type. Design value for nangka wood based on diameter size 4,1; 5,2 and 5,5 mm are 261; 358 and 365 kg respectively, and for rasamala wood the design value is sligthly low, which is 227; 311 and 321 kg respectively. The minimum value becomes fundamental for determining design value of total allowable load per shear plane connection (RT) based on amount of nail (4-10), which is determined by multiply the value of certain type woods with amount of nails used. Key words: double shear, displacement, allowable load per nail per shear plane (R), total allowable load per shear plane (RT)